RECORD OF NIBEA CHUI TREWAVAS FROM INDIA - Jayaprakash, A A (Indian Journal of Fisheries, 2011)
Fishes of the family Sciaenidae OHnprise a number of coounercially important species in the tropical and subtropical waters and a total of IS general coverii^ 45 species have been reported (Druzhinin 107.1) from Indian Ocean.Ftcm seas around India, dtere are 14 genera embracing 30 species (Mohan 1969).